Ответы и объяснения

  • Участник Знаний
2013-03-16T16:59:53+04:00

16c^2-49=0

(4c - 7 ) (4c+7) = 0

один из множителей равен 0

(4c - 7 ) =0 ; c =7/4 =1,75

(4c+7) = 0  ;  c =-7/4 =-1,75

ответ -1,75 ; 1,75

 

(4x-3)(4x+3)-(4x-1)^2=3x

16x^2-9-16x^2+8x-1 -3x=0

5x  -10=0

5x=10

x=2

ответ 2

  • Участник Знаний
2013-03-16T17:25:59+04:00

1) 16c^2-49=0

     (4с+7) (4с-7)=0

     4с+7=0  или  4с-7=0

     4с=-7               4с=7

     с= -7/4             с= 7/4

     Ответ: -7/4, 7/4

2) (4x-3)(4x+3)-(4x-1)^2=3x

     16x^2-9- (16x^2-8x+1)= 3x

      16x^2-9-16x^2+8x-1=3х

       -9+8x-1-=3х 

       8x-10=3х

       8х-3х=10

       5х= 10

       х=2

      Ответ:2